The Effect of Bar Ductility Reinforcement on the Flexural Behavior of Reinforced Concrete Beams - Asiani, Baiq; Djamaluddin, Rudy; Fakhruddin (Engineering, Technology & Applied Science Research, 2026)
This study investigates the influence of reinforcing steel ductility, directly associated with carbon content, on the flexural behavior of reinforced concrete beams. Three beam specimens with identical dimensions (150 mm × 200 mm × 3300 mm) were tested under static loading, each reinforced with steel bars classified as Low-Carbon Steel (LCS), Medium-Carbon Steel (MCS), or High-Carbon Steel (HCS). The experimental program evaluated the load deflection response, load–strain behavior, and crack pattern of each beam. The results show that variations in carbon content significantly affect the ductility and stiffness of reinforced concrete beams. The beam reinforced with LCS exhibited the highest flexural ductility (μ = 4.64), indicating superior plastic deformation capacity and greater energy absorption before failure. MCS and HCS reinforcements produced lower ductility values of 2.84 and 2.19, respectively, corresponding to higher stiffness and more limited deformation beyond yielding. Crack pattern observations confirmed that all beams initially developed flexural cracks, which transitioned into flexure shear cracks at higher load levels. Overall, reinforcing LCS substantially improves strain compatibility, flexural performance, and energy dissipation capacity of reinforced concrete beams. These findings highlight the importance of selecting highly ductile reinforcement to enhance structural safety and seismic resistance.